Role of vitamin D3 on IL-17 expression in colon and improvement of colonic mucosa in an inflammatory bowel disease mice model - Fiona Paramitha; Satrio Wibowo (Indonesian Pediatric Society, 2023)
Background Inflammatory bowel disease (IBD) is an inflammation due to a Th1/Th2 regulatory imbalance and a Th17/Treg transformation imbalance which then releases inflammatory mediators, such as interleukin-17. The administration of vitamin D has the potential to prevent the inflammation in IBD. Objective To evaluate a possible role of vitamin D3 in reducing IL-17 expression and colonic mucosal repair in an IBD mice model. Methods The study used male BALB/c mice, 8-10 weeks old, weighing 20-25 grams, divided randomly into five groups with 8 mices in each group. The experimental mice were given 5% dextran sulfate sodium (DSS) on days 1-7 to induce colitis, and then were given vitamin D3 on days 8-14. Group 1 was the control group; Group 2 was given 5% DSS; Group 3 was given 5% DSS and vitamin D3 0.2 mcg/25 g body weight; Group 4 was given 5% DSS and vitamin D3 0.4 mcg/25 g body weight; and Group 5 was given 5% DSS and vitamin D3 0.6 mcg/25 g body weight. On day 15, the mice underwent euthanasia and colonic retrieval. Parameters assessed were IL-17 expression (immunohistochemical, with monoclonal antibody against IL-17) and colonic histology improvement, using the mouse colitis histology index (MCHI) score. Results The IL-17 expression measured by immunohistochemistry increased significantly in only 5% DSS group. There was a significant decrease in MCHI scores in the groups given vitamin D3, where the greater the dose of vitamin D3 given, the lower the MCHI score. Interleukin-17 expression had positive strong correlation with MCHI (r=0.985; P=0.002) Conclusion The improvement of colonic mucosal damage based on MCHI score was significant in groups given vitamin D3. There is a significant correlation between IL-17 reduction and colonic mucosal repair in IBD mice.